Features of Verbalisation of Semantics of Consequence in Phraseological Picture of the World in the Russian Language - O. V. Kolesnikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the study of phraseological units with semantics of consequence. One of the segments of the concept of CAUSATION is considered, which covers causation, target, conditional and concessional relations. Linguistic and cultural analysis allows to reveal national and cultural peculiarities of verbalization of the mentioned semantics at the level of phraseology. It is shown that phraseological units, which contain the component of consequence in their structure, represent situations of emotional shocks, great physical and mental stress, have causal indicators ot kogo -, ot chego-libo ‘from someone, from something,’ are included in contexts, containing an indication of the cause. The analyzed material confirms the well-known thesis that idioms describing negative emotions prevail in quantitative terms over phraseological units representing positive emotions. The structure of the thematic group of phraseological units involving determination of such semantic groups as “Joy. Delight. Happiness,” “Fear. Horror,” “Anger. Rage,” “Despair,” “Anxiety. Excitement,” “Confusion. Shame,” “Sadness,” “Surprise. Astonishment,” “Suffering. Flour.” The main forms underlying the idioms in the studied groups are described. It is noted that in the structure of phraseological units components serdtse ‘heart,’ dusha ‘soul,’ golova ‘head,’ um ‘mind,’ pamyat’ ‘memory’ symbolizing the emotional and intellectual nature of a person are frequent.